The Effect of WebQuest on Writing Ability: A Case Study of EFL in Indonesia - Sri Wahyuni; Fauzul Etfita; Siska Handayani (STAI Hubbulwathan Duri, 2021)
This research aimed to find out students’ writing at vocational school YPPI Tualang and know how WebQuest improves students’ writing procedure text of second-year students at vocational school YPPI Tualang. This current study was experimental research which was held at the vocational school YPPI Tualang. The experimental research involved two groups of students; they were the experimental group and the control group. The research subjects were the second-year students of vocational school YPPI Tualang. The sample of this research was taken randomly. The experimental group that belongs to the experimental group included 20 students, while the students of the control group belong to the control group were 20 students. The researcher's findings included the research results: the experimental class's analysis results show that the mean score of pre-tests in the experimental class was 63.9. The mean score of the post-test was 77.4. Meanwhile, the control class's analysis result shows that the mean score of pre-tests in the control class was 53.8, and the mean score of the post-test was 58.4. It shows that the experimental class experiences improvement in their writing test. The hypothesis testing indicates that the experimental class students' score was higher than the control class. It can be concluded that WebQuest was effective for enhancing learning writing and providing a positive learning experience.